Treatment patterns and survival of low and intermediate‐risk prostate cancer in end‐stage kidney disease: A retrospective population cohort study. (16th January 2023) - Sarabu, Nagaraju; Dong, Weichuan; Ray, Al W.; Fernstrum, Austin; Prunty, Megan; Ponsky, Lee E.; Shoag, Jonathan E.; Shahinian, Vahakn B.; Lentine, Krista L.; Koroukian, Siran M.
Abstract: Background: In accordance with guidelines, observation with or without active surveillance for low‐risk prostate cancer increased in recent years in the general population. We compared treatment patterns and mortality for low‐ and intermediate‐risk prostate cancer and mortality rates among end‐stage kidney disease (ESKD) and non‐ESKD patients. Methods: This is a retrospective population‐based observational cohort study of Surveillance, Epidemiology, and End Results‐Medicare data of men aged 66 years and older with localized prostate cancer (2004–2015). ESKD status was determined using Medicare billing codes. Multivariable logistic regression models and Cox‐proportional hazards models were used to study definitive treatment patterns and mortality, respectively. Results: For low‐risk prostate cancer, dialysis patients (N = 83) had lower but not statistically significant odds (OR, 0.74; 95% CI: 0.48–1.16) of receiving definitive treatment than non‐ESKD patients ( N = 24, 935). For those with intermediate‐risk prostate cancer, dialysis patients (N = 254) had lower odds to receive definitive treatment (OR, 0.54; 95% CI: 0.42–0.72) than non‐ESKD patients ( N = 60, 883). From 2004–2010 to 2011–2015, for patients with low‐risk prostate cancer, while the receipt of definitive treatment for non‐ESKD patients trended down from 72% to 48%, it trended up for dialysis patients from 55% to 65%. Kidney transplant patients ( N = 33 for low‐risk and N = 91 for intermediate‐risk) had lower rates of definitive treatment for low‐risk and similar rates of treatment for intermediate‐risk prostate cancer compared to non‐ESKD patients. Conclusions: The disparity in definitive treatment rates for low‐risk prostate cancer among dialysis patients exists despite their high mortality, compared to the general population. Abstract : In contrast to the general population, though older dialysis patients have a three times higher mortality, they receive definitive treatments for low‐risk prostate cancer at high rates and these rates have increased in the recent era. Kidney transplant patients do not experience higher prostate cancer deaths in the low‐risk prostate cancer than the general population and hence immunosuppression does not need to sway providers toward definitive treatments.